RESTORATIVE JUSTICE AS ACCESS TO JUSTICE FOR CHILD VICTIMS OF CRIMINAL ACTS IN THE CRIMINAL JUSTICE SYSTEM - Triwati, Ani -; Sukarna, Kadi -; Nuswanto, Heru - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Restorative justice in resolving criminal cases requires justice with balance and peace. Balance obtains justice for perpetrators, victims, and affected communities. Peace aims to restore the situation or relationship that has been fractured between the perpetrator and the child victim and his family, including the recovery of the community affected by the criminal offense. Restorative justice is fundamental for child victims to obtain justice as part of recovery. The type of research used is normative juridical with descriptive-analytical research specifications and qualitative data analysis. Child victims of criminal acts require special protection and treatment to recover both physically and psychologically. Child victims obtain access to justice in a restorative justice approach with the fulfillment of elements including admission of guilt, forgiveness, and restoration of circumstances. For perpetrators of criminal acts, admission of guilt, forgiveness, and compensation are access to peace with the victim.